Residual Stress Analysis for Composite Thermoplastic Woven Material with Unique Bending Moment: Analytical and Finite Element Analysis - Azad Mohammed Ali Saber; Lanja Saeed Omer (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Analytical analysis for assumption of the Bernoulli-Navier hypotheses and finite element method (APDL) are used to detect the residual stress through composite beam under unique bending moment for various elastic-plastic boundaries. A woven steel fibers with various orientation angles (0o, 15o, 30o, 45o, 60o, and 90o) is assumed in this analysis. The governing differential equation and the boundary conditions are both resolved analytically for plane stress case and tiny plastic deformations. The yield criterion is based on the Tsai-Hill theory. It is observed that; the residual stress intensity is strongest at the top and bottom roofs of the beam. A good agreement is found between analytical and finite element method for several moments and elastic-plastic boundary h.